Peran Biah Arabiyah dalam Meningkatakan Kecapakan Berbahasa Arab di Pondok Pesantren - Huda, Samsul (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2025)
The language environment (biah lughawiyah) plays a crucial role in enhancing speaking skills and linguistic literacy in Arabic among students and pesantren communities. This study aims to describe and analyze the role of the Arabic language environment in the learning process at Darullughah Wadda’wah Islamic Boarding School. The research employs a qualitative case study approach conducted at Darullughah Wadda’wah, Bangil, Pasuruan. The findings indicate that the deep internalization of a strong Arabic-speaking culture and the systematic development of a language-rich environment have established a language culture that is embedded into the daily life of the pesantren. This well-maintained environment significantly facilitates students' active and fluent mastery of Arabic. The contribution of this research emphasizes the importance of managing a language environment to improve Arabic language learning quality in pesantren and related educational institutions.